Banners of the Northern Saints, 600-1500 - Sharpe, R (2015)
Relates the history of the late medieval banners of St Cuthbert and St John of Beverley, the thee saints' banners at the battle of the Standard, and the claims made by the churches of York, Beverley, and Ripon to military exemption by the service of their saints' banners alone to the historiography on banners as a symbol of the church's engagement in warfare in the eleventh and twelfth centuries. The role of the banners of St Cuthbert and St John in battles against the Scots can be traced in detail, and its background can be followed through the hagiography of St John of Beverley.